Sarcoidosis and the mTOR, Rac1, and Autophagy Triad. Issue 4 (April 2020) - Pacheco, Yves; Lim, Clarice X.; Weichhart, Thomas; Valeyre, Dominique; Bentaher, Abderrazzak; Calender, Alain
Abstract : Sarcoidosis is an enigmatic multisystem disease characterized by the development and accumulation of granulomas: a compact collection of macrophages that have differentiated into epithelioid cells and which are associated with T helper (Th)1 and Th17 cells. Although no single causative factor has been shown to underlie sarcoidosis in humans, its etiology has been related to microbial, environmental, and genetic factors. We examine how these factors play a role in sarcoidosis pathogenesis. Specifically, we propose that dysfunction of mTOR, Rac1, and autophagy-related pathways not only hampers pathogen or nonorganic particle clearance but also participates in T cell and macrophage dysfunction, driving granuloma formation. This concept opens new avenues for potentially treating sarcoidosis and may serve as a blueprint for other granulomatous disorders. Highlights: Sarcoidosis is a granulomatous disease triggered by genetic, microbial, and environmental factors. Familial sarcoidosis cases allow the identification of pathways involved in genetic predisposition to the disease. Macrophage and T cell dysfunction contributes to the development and progression of sarcoidosis. We propose that defects in autophagy and mTOR-related pathways decrease the clearance of infectious as well as nonorganic particles and promote granuloma formation and Th17 differentiation in sarcoidosis. Drugs used in sarcoidosis management, such as methotrexate, azathioprine, leflunomide, and chloroquine, interfere with autophagy. Functional studies using mutated forms of genes involved in the mTOR, Rac1, and autophagy pathways are warranted to identify cell types and underlying mechanisms contributing to disease development.